PROFIL PELAJAR PANCASILA UNTUK SISWA SEKOLAH DASAR DALAM PERSPEKTIF SUSASTRA HINDU (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The purpose of the research is to understand the Pancasila Student Profile (Profil Pelajar Pancasila) in Hindu literature either Sruti as well as Smerti. The research is using literature review method. The result of the research showed that the Weda characteristics are flexible so that they can be applied throughout the entire time. The Weda characteristics could answer different challenges in different era, in this case the challenges are in globalization era and industrial revolution 4.0. The six dimensions of Pancasila Student Profile consist of (1) global unity (berkebhinekaan tunggal), (2) mutual cooperation, (3) creative, (4) critical thinking, (6) independency and (6) religious, having faith to the God Almighty, and noble character, all of them are explicitly and implicitly written in Hindu literature, in Pustaka Suci Atharwa Weda, Bhagavad Gita, Rg Veda, Wrhaspati Tattwa, Sarsamuccaya, Lontar Siwa Sasanà, Manawa Dharma Sastra, dan Kekawin Niti Sastra